Discordant biochemical parameters of acromegaly remission do not influence the prevalence or aggressiveness of metabolic comorbidities: a single-center study - Romanisio, Martina; Pitino, Rosa; Ferrero, Alice; Pizzolitto, Francesca; Costelli, Samuele; Antoniotti, Valentina; Marzullo, Paolo; Aimaretti, Gianluca; Prodam, Flavia; Caputo, Marina (Frontiers in Endocrinology, 2023)
Acromegaly is a rare pathology caused by a growth hormone (GH)-secreting pituitary adenoma, leading to liver hyperproduction of insulin-like growth factor 1 (IGF-1), resulting in somatic modifications and systemic manifestations. Active disease is complicated by increased mortality, in particular for cardiovascular complications. Usually, levels of GH and IGF-1, biomarkers of disease's activity, are congruent, however, in up to 25% of surgically treated patients, discordant GH and IGF-1 levels have been described. The impact of discordant GH and IGF-1 values on acromegaly metabolic complications is a matter of debate. We did not find differences in the prevalence and severity of diabetes, arterial hypertension and dyslipidemia in surgically treated acromegalic patients with disease control and incongruent GH and/or IGF-1 levels compared to those with concordant values. Thus, in absence of other parameters suspected for an active disease, patients with discordant values do not need a closer follow-up to reduce the risk of cardiovascular complications that, finally, affect survival. These findings should support the proper phenotyping of acromegaly, characterized by a complex systemic scenario, and are crucial in order to help the clinicians to ensure the optimal delivery of care and management of the disease, avoiding overmedicalization, relieving the anxiety of patients that lead, finally, to a better quality of life.